PELECEHAN SEKSUAL ANTAR ANAK DALAM PERSPEKTIF HUKUM PIDANA - Ladin, L. (Ahkam: Jurnal Hukum Islam, 2016)
Decency crime in general is an act or acts of violating decency or immoral intentionally damaging public decency or others is not volition, the victim, by force and by threats of violence. Laws threaten punishment for anyone who violates the act. Meanwhile, the intended public is for example in school buildings, a bunch of people, places that can circulate to each person, and so on. Through a variety of media can be seen almost every day crimes with various kinds. Similarly, the perpetrators themselves, anyone can be a perpetrator of a crime, whether the perpetrators are still children, older people, both men and women. So regardless of age or gender, although in reality the number of crimes committed by children is relatively small, but it cannot be denied that the crimes committed by these children happen everywhere. As crime decency committed by minors, it is certainly influenced by many factors, among others, because the child does not receive affection from their parents, parents forget themselves as parents being too busy, also caused by certain parties that is not responsible for, the influence of the environment, freedom of association as a result of not getting attention from their parents at home, their freelance film and video sensors, readings can damage the child’s psyche. Kata kunci: Pelecehan Seksual, Anak, Tinjauan Hukum Pidana